Meningkatkan Kepercayaan Diri Anak Panti Asuhan di LKSA Naungan Kasih Kemuliaan yang Menjadi Korban Bullying - Lisna Sahara; Mia Aulina Lubis (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Orphanages are places to get a safe environment to grow and develop, but orphanages are often places that face psychosocial challenges, such as social stigma, traumatic experiences due to bullying, which have an impact on decreasing self-confidence and difficulty adapting to the social environment. In this PKL, interventions are carried out systematically using the social work casework method, which includes the stages of engagement, assessment, planning, intervention, evaluation and termination. The individual counseling model and cognitive behavioral therapy are focused on providing emotional support, as well as developing adaptive coping strategies. The results of the activities showed a significant increase in the self-confidence and emotional management skills of children who were victims of bullying, where they began to be able to change negative mindsets to be more positive and optimistic. The success of this intervention was supported by the active involvement of social workers, a more supportive atmosphere in the orphanage, and consistency in providing emotional support. Thus, the individual counseling model and cognitive behavioral therapy have proven effective in helping orphanage children overcome the impact of bullying and build better self-confidence to support their optimal development in the future.